Sistem Pencarian Jurnal Ilmiah Cross Language dengan Metode Vector Space Model (VSM) - Indah Mutia Ayudita; Indriati Indriati; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Scientific journals are periodical publications that contain scientific papers with data and information written in accordance with the rules of scientific writing. Scientific journals used widely as a reference to make a new research or continue the previous research. As the usage is growing, scientific journals also easier to find digitally and available in a digital library such as Science Direct and IEEE, but the searching process is still limited to Monolingual Information Retrieval, in which the search results have the same language as the query inputted, even though the relevant documents also available in other languages. This research is done to observe the result of implementing Cross Language Information Retrieval that can do the searching process in one language for the input and retrieved document in two languages. The final result is 8 out of 10 queries have a higher precision up to 74,5% and recall up to 41,5%. Generally, system can retrieved the relevant documents in average for 84%.